The Moderating Role of Gender: Effects of Perceived Green Packaging and Eco-Literacy on Willingness to Pay Through Green Trust - Lopes Amaral, Maria Augustin; Watu, Engelbertus G. Ch; Fallo, Apryanus; da Costa, Teresinha Cardoso (Universitas Brawijaya, Indonesia, 2026)
Single-use plastic packaging is a serious environmental problem because it is difficult to break down and contributes to pollution. Lontar packaging is widely used in the city of Kupang, Indonesia, and has the potential to be a more sustainable alternative. However, consumers may not be prepared to pay a premium for products packaged with lontar unless they trust the packaging's environmental benefits. The study investigated the impact of perceived green packaging and eco-literacy on consumer readiness to pay a premium for lontar-packaged products through green trust. It also investigated whether these interactions differed between male and female consumers. The method employed is a quantitative survey of 200 consumers who have purchased or used products with lontar packaging. The data were examined using partial least squares structural equation modelling (PLS-SEM). Results indicate that perceived green packaging does not directly improve willingness to pay. However, perceived green packaging has a considerable positive effect on green trust, and green trust positively influences willingness to pay. Also, Eco-literacy is positively associated with green trust and willingness to pay. The multi-group study demonstrates that gender moderates the impact of perceived green packaging and eco-literacy on willingness to pay, and the effects are larger for male consumers. These results imply that firms should not only promote the environmental friendliness of lontar packaging but also provide clear information regarding the quality, safety, cleanliness, and environmental benefits of lontar packaging. This can increase consumer confidence and facilitate acceptance of premium costs.